Assessing functioning in adolescents with chronic fatigue syndrome: psychometric properties and factor structure of the School and Social Adjustment Scale and the Physical Functioning Subscale of the SF36. Issue 5 (1st September 2020) - Loades, M.E.; Vitoratou, S.; Rimes, K.A.; Chalder, T.
Abstract: Background: Chronic fatigue syndrome (CFS) has a major impact on functioning. However, no validated measures of functioning for this population exist. Aims: We aimed to establish the psychometric properties of the 5-item School and Social Adjustment Scale (SSAS) and the 10-item Physical Functioning Subscale of the SF-36 in adolescents with CFS. Method: Measures were completed by adolescents with CFS ( n = 121). Results: For the Physical Functioning Subscale, a 2-factor solution provided a close fit to the data. Internal consistency was satisfactory. For the SSAS, a 1-factor solution provided an adequate fit to the data. The internal consistency was satisfactory. Inter-item and item-total correlations did not indicate any problematic items and functioning scores were moderately correlated with other measures of disability, providing evidence of construct validity. Conclusion: Both measures were found to be reliable and valid and provide brief measures for assessing these important outcomes. The Physical Functioning Subscale can be used as two subscales in adolescents with CFS.